Promoting inclusion in education abroad : a handbook of research and practice - Hamir, Heather Barclay; Gozik, Nick (Sterling, Virginia : Stylus Publishing, 2018)
'This volume offers a combination of research-based chapters and case studies from leading experts on the barriers that disproportionately impact specific groups of students, including: students with disabilities; first-generation college students; undocumented students; racial and ethnic minorities; science, technology, engineering, and mathematics (STEM) majors; and males. The authors illuminate the issues which may inhibit education abroad participation, from individual to institutional, and present strategies reflecting a broad range of institutional contexts, resources, and needs. While there has been significant discussion and action to promote broader inclusion in education abroad, this is the first volume focusing on research and practice to achieve these ends, and is intended as a critical resource for practitioners and scholars alike'--
Making the case for inclusion in education abroad -- Underrepresentation in education abroad: a review of contemporary research and future opportunities -- Students of color and study abroad: from barriers to results -- First-generation college students and study abroad: examining the participation gap and successful strategies for promoting access -- There and back again: a study abroad journey with men -- Commitments that work: removing barriers for students with disabilities in education abroad -- Promoting education abroad among community college students: overcoming obstacles and developing inclusive practices -- Strategies for mobilizing students in the sciences: a case study -- Engineers abroad: opportunities for sophomores in international education -- Undocumented students and access to education abroad -- A way forward: exploring strategies at multiple levels -- Expanding the reach of education abroad: recommendations for research, policy, and practice.
Includes bibliographical references and index.
Keywords: Foreign study -- Handbooks, manuals, etc; Inclusive education -- Handbooks, manuals, etc